Lower Limb Task-Based Functional Connectivity Is Altered in Stroke - Vinehout, Kaleb (Brain Connect, 2019)
The goal of this work was to examine task-dependent functional connectivity of the brain in people with stroke. The work was motivated by prior observations indicating that, during pedaling, cortical activation volume is lower in people with stroke than controls. During paretic foot tapping, activation volume tends to be higher in people with stroke than controls. This study asked whether these differences could be explained by altered network function of the brain. Functional magnetic resonance imaging was used to examine local and global network function of the brain during tapping and pedaling in 15 stroke and 8 control participants. Independent component analysis was used to identify six task regions of interest (ROIs) in the primary sensorimotor cortex (M1S1), anterior lobe of cerebellum (AlCb), and secondary sensory cortex (S2) on the lesioned and non-lesioned sides of the brain (left, right for controls). Global connectivity was calculated as the correlation between mean time series for each ROI. Local connectivity was calculated as the mean correlation between voxels within each ROI. Local efficiency, weighted sum, and clustering coefficient were also calculated. Results suggested that local and global networks of the brain were altered in stroke, but not in the same direction. Detection of both global and local network changes was task-dependent. We found that global network function of the brain was reduced in stroke participants as compared with controls. This effect was detected during pedaling and nonparetic tapping, but not during paretic tapping. Local network function of the brain was elevated in stroke participants during paretic tapping and reduced during pedaling. No between-group differences in local connectivity were seen during nonparetic tapping. Connections involving S2, M1S1, and AlCb were significantly affected. Reduced global connectivity of the brain might contribute to reduced brain activation volume during pedaling poststroke.